Faktor Risiko Yang Berhubungan Dengan Kejadian Infeksi Luka Operasi (ILO) Pasca Operasi Lumbal Pada Bedah Ortopedi: Risk Factors Associated with the Incidence of Surgical Wound Infection (ILO) Post Lumbar Surgery in Orthopedic Surgery - Sulistyani Prabu Aji; Suryo Ediyono (YCMM, 2022)
Surgical wound infection (ILO) is one of the most common nosocomial infections that occur after surgery. One of the important roles in efforts to reduce the ILO is to prevent the occurrence of risk factors. This research design uses Systematic Review with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). One of the conclusions obtained is that the risk factors for post-operative wound infection orthopedic surgery are patient and environmental factors.